Effects of culture conditions on the production of inulinase by Kluyveromyces marxianus - Marcia Luciana Cazetta (Brazilian Archives of Biology and Technology, 2010)
The present study was conducted to investigate the influence of initial sucrose concentration, pH and aeration rate on biomass and inulinase production by Kluyveromyces marxianus var. bulgaricus in a stirred batch reactor. Maximum inulinase activity (15.29 UmL-1) was obtained at a sucrose concentration of 10 g L-1, pH 5.0 and aeration rate of 1 vvm. The 20 g L-1 sucrose concentration was suitable for cell growth; however, enzymatic activity at this concentration was inhibited due to catabolic repression. The increase in aeration rate caused a reduction in enzyme activity with no relevant biomass increase. O estudo foi conduzido para investigar a influência da concentração inicial da sacarose, a taxa da aeração e do pH na biomassa e na produção da inulinase pela Kluyveromyces marxianus var. bulgaricus em um reator em batelada. A máxima atividade de inulinase, 15.29 UmL-1, foi obtida na concentração de 10 g L-1 de sacarose, no pH 5.0 e na taxa da aeração de 1 vvm. A concentração de sacarose de 20g L-1 foi apropriada para o crescimento celular, porém nesta concentração a atividade enzimática foi inibida, devido a repressão catabólica. O aumento na taxa da aeração propiciou redução da atividade enzimática, ao mesmo tempo em que não houve aumento considerável do biomassa.